STRUKTUR TEKS MEDIA DARING PRANCIS DALAM PEMBERITAAN MENGENAI NIIS (Suatu Analisis Wacana Kritis) - Fadhil, Ahmad; hasyim, muhammad; wahyuddin, wahyuddin (JURNAL ILMU BUDAYA, 2015)
The title of this research is the text structure of French online media in the newsof Islamic Stateof Iraq and Syam (ISIS). The aim of this research is to analyse the structure of the French onlinemedia texts to obtain an overview of the macrostructure, the superstructure and themicrostructure of the text which could define ideology differences from each French onlineMedias.To answer several problems of this research, the methods of descriptive qualitative is applied,based on critacal discourse analysis theory of Teun A van Dijk which divide the text structureinto three levels; macrostructure, superstructure and microstructure. The conclusion of thisresearch is that each French online media construct the discourse of ISIS with different ways ofinterpretation based on their ideology which appears clearly in the difference of news text ineach level of structure text.Keywords: macrostructure, superstructure, microstructure, ideology, interpretation